2009
DOI: 10.1007/s12311-009-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Purkinje Cell Death Is Spatiotemporally Organized in the Developing Mouse Cerebellum

Abstract: Physiological cell death is crucial for matching defined cellular populations within the central nervous system. Whereas the time course of developmental cell death in the central nervous system is well analyzed, information about its precise spatial patterning is scarce. Yet, the latter one is needed to appraise its contribution to circuit formation and refinement. Here, we document that during normal cerebellar development, dying Purkinje cells were highly localized within the vermal midline and in a lobule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 71 publications
4
42
0
Order By: Relevance
“…After vigorous washings, sections were incubated with the secondary antibody solution (Alexa Fluor 488-and Alexa Fluor 546-conjugated goat anti-mouse and anti-rabbit antibodies, 1:500 in PBS; Invitrogen) at room temperature for 2 h. Finally, sections were counterstained using Hoechst 34580 (1 g/ml PBS, 5 min), washed for at least 1 h, and embedded in Mowiol. Although calbindin and MBP immunohistochemical stainings are well established (BouslamaOueghlani et al, 2003;Jankowski et al, 2009), we checked for merlinspecific staining using several procedures. First, omitting the primary antibody revealed no signal; and second, incubating sections with a merlin-specific peptide (10-fold excess) diminished the specific binding to background levels (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…After vigorous washings, sections were incubated with the secondary antibody solution (Alexa Fluor 488-and Alexa Fluor 546-conjugated goat anti-mouse and anti-rabbit antibodies, 1:500 in PBS; Invitrogen) at room temperature for 2 h. Finally, sections were counterstained using Hoechst 34580 (1 g/ml PBS, 5 min), washed for at least 1 h, and embedded in Mowiol. Although calbindin and MBP immunohistochemical stainings are well established (BouslamaOueghlani et al, 2003;Jankowski et al, 2009), we checked for merlinspecific staining using several procedures. First, omitting the primary antibody revealed no signal; and second, incubating sections with a merlin-specific peptide (10-fold excess) diminished the specific binding to background levels (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Maloku et al (2010) have also found a similar PC loss in adult reelin-haploinsufficient mice, and have interpreted their findings in the context of reelin deficiency and cerebellar abnormalities observed in schizophrenia, thus underscoring the links between reelin and psychosis. The question why reelin haploinsufficiency leads to cell loss in the male but not in the female cerebellum, and how high levels of estradiol at P5 inhibit cell loss, cannot be answered yet, but recent data indicate that PCs show a peak of apoptosis during the first postnatal week in the mouse (Jankowski et al, 2009). It is tempting to speculate that PC loss in rl/+ mice is due to apoptosis, and that estradiol inhibits cell death by increasing reelin expression.…”
Section: Implications For the Neurobiology Of Asdmentioning
confidence: 99%
“…On the other hand, to be considered as an apoptotic PC, the structure observed had to fulfill the following criteria: (a) one or more fragments of highly condensed chromatin (within or reminiscent of a pyknotic nucleus) and distinct from the PC nucleolus, and (b) position within the PC layer [16].…”
Section: Quantitative Analysesmentioning
confidence: 99%
“…Two time windows have been reported: in the first of these, apoptotic figures have been found at E15 [2]. In the second, dying PCs are seen from birth until P10 [16,19,25]. Thus, whereas the timing and extent of dying PCs have been addressed [16], to our knowledge, no attempts have been made to determine whether physiological PC death is related to its time of origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation